2019
DOI: 10.14739/2310-1210.2019.5.179473
|View full text |Cite
|
Sign up to set email alerts
|

Features of pregnancy course in women with chemoresistant tuberculosis (a literature review)

Abstract: Особливості перебігу вагітності в жінок, які хворі на хіміорезистентний туберкульоз (огляд літератури) О. М. Разнатовська, O. С. Шальмін Туберкульоз -глобальна причина захворюваності серед жінок репродуктивного віку, що становить серйозну материнську та перинатальну небезпеку як у розвинених країнах, так і країнах, що розвиваються. Туберкульоз посідає 3 місце серед причин смертності жінок репродуктивного віку. При цьому спостерігається майже однакова частота як діагностики специфічного процесу у вагітних, так … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Initiation during third trimester had 100.0% live births. Similarly, a favourable birth outcome was also associated with DR-TB treatment initiation during the second trimester in a Ukraine study [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initiation during third trimester had 100.0% live births. Similarly, a favourable birth outcome was also associated with DR-TB treatment initiation during the second trimester in a Ukraine study [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following a literature review [6], we concluded that pregnant women with tuberculosis (TB) infection have a significantly higher risk of developing complications such as premature birth, maternal and perinatal mortality and neonatal outcomes include intrauterine growth retardation, congenital anomalies, respiratory distress syndrome and other. Based on these facts, most researchers recommend the initiation of second-line drugs for MDR-TB according to drug susceptibility test (DST) results since the second trimester of pregnancy avoiding amikacin, streptomycin, prothionamide ключевые слОва: беременность, мультирезистентный туберкулез, ВИЧ-инфекция, бедаквилин.…”
Section: клінічний досвідmentioning
confidence: 99%